2020
DOI: 10.3390/cancers12082191
|View full text |Cite
|
Sign up to set email alerts
|

Development of [18F]ICMT-11 for Imaging Caspase-3/7 Activity during Therapy-Induced Apoptosis

Abstract: Insufficient apoptosis is a recognised hallmark of cancer. A strategy to quantitatively measure apoptosis in vivo would be of immense value in both drug discovery and routine patient management. The first irreversible step in the apoptosis cascade is activation of the “executioner” caspase-3 enzyme to commence cleavage of key structural proteins. One strategy to measure caspase-3 activity is Positron Emission Tomography using isatin-5-sulfonamide radiotracers. One such radiotracer is [18F]ICMT-11, which has pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…These are small molecules that form a reversible covalent bond in the active site of caspase-3 and -7 with high affinity by nucleophilic attack of the caspase cysteine at the 3-carbonyl group of the isatin moiety, which corresponds to the warhead of the molecule [ 24 , 25 ]. Their nanomolar affinity to caspase-3/7, with IC 50 values ranging from 0.5 to 80 nM for caspase-3 ( Table 1 ), and their low molecular weight made them good probe candidates to image caspase-3/7 activity [ 24 , 26 ]. They are, however, often prone to metabolic degradation.…”
Section: Small Molecule Probesmentioning
confidence: 99%
See 2 more Smart Citations
“…These are small molecules that form a reversible covalent bond in the active site of caspase-3 and -7 with high affinity by nucleophilic attack of the caspase cysteine at the 3-carbonyl group of the isatin moiety, which corresponds to the warhead of the molecule [ 24 , 25 ]. Their nanomolar affinity to caspase-3/7, with IC 50 values ranging from 0.5 to 80 nM for caspase-3 ( Table 1 ), and their low molecular weight made them good probe candidates to image caspase-3/7 activity [ 24 , 26 ]. They are, however, often prone to metabolic degradation.…”
Section: Small Molecule Probesmentioning
confidence: 99%
“…[ 18 F]ICMT-11 was evaluated in many preclinical tumor models, using various cell lines and treatments [ 26 ]. These preclinical studies had varying results but generally showed a 1.5- to 2.5-fold higher uptake of the radiotracer in treated tumors compared to controls.…”
Section: Small Molecule Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…Caspases belong to the cysteine proteases family and are intricately involved in the apoptotic process. In fact, activating the “executioner” caspase-3 enzyme initiates the breakdown of major structural proteins within the cell [ 19 ]. Based on our results, GA exposure markedly increased Caspase-3/7 activity ( Figure 3a ).…”
Section: Resultsmentioning
confidence: 99%
“…The half-lives of isotopes used in PET or SPECT tracers are usually short, posing a unique barrier to commonplace application of these modalities for protease imaging. Nevertheless, the technology was successfully demonstrated for imaging metalloproteases [ 263 , 264 , 265 ], cysteine cathepsins [ 266 , 267 , 268 ] and caspases [ 269 , 270 ] in preclinical settings. In CT imaging modalities, X-rays are used to create cross-sectional images with high resolution and this technique is widely used for noninvasive clinical imaging [ 271 ].…”
Section: Monitoring Protease Activity In Cancermentioning
confidence: 99%